DISTRIBUTION OF ALLERGENIC PLANTS IN RUSSIA - Tatiana V. Dikareva; Vadim Yu. Rumiantsev (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2015)
We analyzed, for the first time ever, the geographical distribution of the main allergenic plants in Russia. All materials were organized as database and attached to the map in GIS Mapinfo. For each region of Russian Federation, two indices were calculated: the total number of allergenic plants in the region and the “allergenic index”. A series of maps wascompiled: the number of spring-flowering species, the number of summer-flowering species,the total number of species flowering during the whole year, the overall allergen danger during spring and summer seasons, respectively, and the overall allergen danger during the whole year. In terms of the number of allergenic species and by the “allergenic index,” the most dangerous regions appeared to be the Ryazan and Voronezh Oblasts, while the less dangerous – the Chukotka Autonomous Okrug, and the Magadan Oblast. The maps may serve as a reference source for allergologists and allergy sufferers.